2019
DOI: 10.1007/s10784-019-09432-z
|View full text |Cite
|
Sign up to set email alerts
|

Institutional diffusion for the Minamata Convention on Mercury

Abstract: A trinity composed of legally binding regulations, an independent financial mechanism, and a compliance mechanism characterizes the institutional design of the Minamata Convention on Mercury. Meanwhile, few existing environmental treaties feature an independent financial mechanism as well as a compliance mechanism. Why did the Minamata Convention acquire two mechanisms? There are two rival hypotheses on uncertainty about institutional consequences and international agreements. The rational design school posits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…9,10 The Convention's advantage over other environmental conventions is that it includes a tripartite institutional design comprising legally binding regulations, an independent financial mechanism, and a compliance mechanism. 11 As the international movement to phase out mercury gains momentum, concerns about international mercury trade are increasing. 12 Article 3 of the Convention includes provisions to control international mercury trade and adopts a prior informed consent procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The Convention's advantage over other environmental conventions is that it includes a tripartite institutional design comprising legally binding regulations, an independent financial mechanism, and a compliance mechanism. 11 As the international movement to phase out mercury gains momentum, concerns about international mercury trade are increasing. 12 Article 3 of the Convention includes provisions to control international mercury trade and adopts a prior informed consent procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Our society is phasing out mercury through international environmental regulations because of its damaging effects on human health and ecosystems. Regulations targeting mercury-added products include the End-of-Life Vehicles (ELV) directive of 2003, the Restriction of Hazardous Substances (RoHS) directive of 2006 in the European Union (EU), and the Electronic Waste Recycling Act (EWRA) of 2007 in California. Additionally, the EU and the United States have directly banned the exports of mercury since 2011 and 2013, respectively. , To control mercury’s anthropogenic life cycle internationally, including mining, international trade, production, use, and waste management, the Minamata Convention on Mercury (hereafter, “Convention”) was adopted in 2013. , The Convention came into force in 2017 and currently includes 137 party countries. , The Convention’s advantage over other environmental conventions is that it includes a tripartite institutional design comprising legally binding regulations, an independent financial mechanism, and a compliance mechanism . As the international movement to phase out mercury gains momentum, concerns about international mercury trade are increasing…”
Section: Introductionmentioning
confidence: 99%
“…Since cooperation under the Minamata Convention was initiated upon its adoption, a prior institution for inter-organizational cooperation outside the Minamata Convention could influence their cooperative arrangements. Uji (2019) found that experiences implementing chemicals treaties, including the Stockholm and Rotterdam treaties, influenced the institutional design for the Minamata Convention. 1 Therefore, it is likely that cooperation between IOs on one environmental issue can influence cooperation on another.…”
Section: Introductionmentioning
confidence: 99%